Digital Marketing Data Mapping using bibliometric Analysis - Maulana, Muhammad Rafli; Irawan, Ade; Setiawan, Adi; Agustina, Agustina (Malikussaleh University, Aceh, Indonesia, 2025)
This research examines the importance of digital data marketing as a response to technological advances and changes in the macro environment. The main focus of this research is the role of technologies, such as big data, artificial intelligence (AI), and predictive analytics, in driving successful marketing strategies, particularly for small and medium-sized enterprises (SMEs).To achieve this goal, the researcher used a qualitative research method with a historical approach, aiming to identify trends and developments in the relevant literature. In addition, bibliometric analysis was applied with the help of the VOSviewer tool. This analysis observed a significant growth in the study of digital data marketing. From the search using Publish or Perish covering the period of 1951 to 2025, a total of 1. 354 relevant articles were found. A focus on keyword co-occurrence revealed 6,260 keywords related to digital data marketing. After filtering the keywords into those that appeared at least three times and eliminating less relevant terms, 284 were found and divided into 16 clusters. This bibliometric analysis provides valuable insights for developing digital data marketing research through clear visualization of trends.